Enlightenment in The Age of Phillis — The Age of Phillis (Roundtable) - DeLucia, JoEllen (2021)
During one of the earliest conversations in our reading group, we spent time consid-ering the title of Jeffers’s collection, The Age of Phillis. For our group primarily comprising teachers and scholars of eighteenth-century British and American litera-ture, the title instantly evoked the names of classes we had both taken and later taught: “The Age of Reason,” “The Age of Enlightenment,” “The Augustan Age,” and “The Age of John-son.” Of course, these standard frameworks were designed to mark a range of different shifts in the history of aesthetics and the history of ideas. “The Age of Enlightenment” or “The Age of Reason” often traces a movement from a theistic worldview toward what David Hume fa-mously called “the science of man”; “The Augustan Age” tracks a revival of ancient Greece and Rome as aesthetic models for an increasingly commercial and democratic eighteenth cen-tury; and “The Age of Johnson,” using Samuel Johnson as a model, charts the rise of the pro-fessional author. The Age of Phillis disrupts these standard narratives and invites scholars and teachers to rethink how the study of the eighteenth century is structured. What does the eight-eenth century look like when we center the experience of Phillis Wheatley Peters instead of Enlightenment philosophy, neoclassical poetics, or Samuel Johnson? What happens if instead of teaching Wheatley Peters as the conclusion of a unit on, say, Enlightenment rights dis-course that begins with Thomas Paine or Mary Wollstonecraft, we instead start with her?